Implementation of the Fetal Monitor Safety Nurse Role: Lessons Learned. Issue 5 (September 2019) - Griggs, Kellie M.; Woodard, Elizabeth K.
Abstract: Background: The fetal monitor safety nurse role was created as a supplemental support for nurses assessing fetal heart rate tracings in response to an adverse event. An experienced labor and delivery nurse without a patient care assignment was designated to continuously assess all active fetal monitoring tracings, via an electronic display away from the main nurses' station, as an adjunct to the care and assessment of the nurse with primary responsibility for the patient. Purpose: The purpose of this project was to evaluate the views of nurses who served as fetal monitor safety nurses about various aspects of the role. Methods: Nurses who served as fetal monitor safety nurses were invited to attend a small group session where they completed a survey about the role and then received information on the importance of fetal monitoring safety. Two weeks later, they were asked to take the survey again to evaluate potential changes in viewpoints. Results: Thirty nurses attended small group sessions and completed the survey. Of those, 22 nurses completed the post survey 2 weeks later. There was minimal change in nurses' views of the fetal monitor safety nurse role after attending the small group sessions. Nurses expressed comfort in notifying peers about concerns related to the fetal heart rate tracing and perceived overall safety benefits; however, they felt that safe staffing measures were not in place to support the role. Concerns were expressed about a nurse being in a nondirect patient care position during times of high census and acuity. Clinical Implications: The fetal monitoring safety nurse may be an innovative potential solution to minimize risk of adverse events during labor that are related to accurate assessment of electronic fetal monitoring data and timely and appropriate interventions. More data are needed on improvements in fetal outcomes and adverse events potentially related to the fetal monitor safety nurse role. Budgetary support and adequate nurse staffing are required to make the role operationally feasible and safe. Valuing and seeking nurses' input as bedside experts about perinatal safety initiatives should be a part of implementing new practices. Abstract : The fetal monitoring safety nurse role, an innovative strategy to promote safer care during labor and birth, is described and evaluated by nurses who served in the role. Full budgetary support for the position is necessary to realize the potential benefits. Nurses appreciated the additional assistance in fetal heart rate tracing assessment, however felt that modifications in nurse staffing were required to make the new role operationally feasibile and effective.